Coefficient inequalities for classes of uniformly starlike and convex functions - Owa, Shigeyoshi; YAVUZ, EMEL; POLATOĞLU, YAŞAR (My University, 2006)
In view of classes of uniformly starlike and convex functions in the open unit discUwhich was considered by S. Shams, S.R. Kulkarni and J.M. Jahangiri, some coefﬁcient in-equalities for functions are discussed
Keywords: Uniformly starlike; Uniformly convex